Adipose-derived stem cells improve tendon repair and prevent ectopic ossification in tendinopathy by inhibiting inflammation and inducing neovascularization in the early stage of tendon healing - Kokubu, Saeko (Regen Ther, 2020)
INTRODUCTION: Achilles tendinopathy is characterized by scar formation or ectopic ossification, both of which result in pain and worsened physical function in athletes and older people. Although cell therapy using adipose-derived stem cells (ASCs) has been shown to be effective for tendinopathy, the underlying mechanisms by which ASCs result in tendon healing in vivo have not yet been fully clarified. METHODS: ASCs were obtained from the fat pads of EGFP transgenic mice by collagenase digestion. C57BL/6 mice were used in a collagenase-induced injury model. ASCs were transplanted into injury sites at 1 week after injury. Tendons were harvested at 9 days, 2 weeks, and 4 weeks after transplantation, and analyzed by histological examination and μCT scanning. RESULTS: Histological analysis and μCT scanning revealed greater recovery of collagen fibers and suppression of ectopic ossification in the ASC-treated group than in the control group at 2 and 4 weeks after injury. Immunohistochemical analysis identified transplanted ASCs in the tendon core close to peritenon and connective tissue at 2 days and 1 week after transplantation, but not at 3 weeks. Furthermore, while the expression levels of IL-1β, GLUT1, and CA9 were significantly reduced in the ASC group compared to the control group at 9 days after injury, those of VEGF and the number of CD31 positive vessels were significantly increased. CONCLUSION: The efficacy of ASCs for tendon repair and the prevention of ectopic ossification in Achilles tendinopathy were demonstrated. Our data suggest that ASCs can modulate inflammation and induce neovascularization in the early stage of tendon injury.